(untitled) - Mogck, Brian David (Malden, MA, 2008)
Writing to Reason presents the principles of writing a clear and well-argued philosophy paper in an easily-referenced numerical format, which facilitates efficient grading and clearer communication between instructors and students.
Keywords: Philosophy,English language,Anh ngữ; Authorship,Writing,Viết